Transcatheter Double Valve-in-Valve Replacement of Aortic and Mitral Bioprosthetic Valves - Savoj, Javad (Cardiol Res, 2019)
Transcatheter aortic valve replacement (TAVR) is an evolving method which has become the treatment of choice in high-risk patients with severe aortic stenosis. Unlike TAVR, the experience with transcatheter mitral valve replacement (TMVR) remains at an early stage because of challenges of valve development and possible complications such as valve displacement and subsequent left ventricular outlet tract (LVOT) obstruction. Here we report a case of transcatheter double valve-in-valve replacement (TDVIVR) in a patient with severe mitral and aortic bioprosthetic valve stenosis, followed by an extensive literature review of the latest techniques and challenges in this field.